2020
DOI: 10.1007/s10815-020-01789-4
|View full text |Cite
|
Sign up to set email alerts
|

Between-laboratory reproducibility of time-lapse embryo selection using qualitative and quantitative parameters: a systematic review and meta-analysis

Abstract: Purpose To investigate the between-laboratory reproducibility of embryo selection/deselection effectiveness using qualitative and quantitative time-lapse parameters. Methods A systematic search was performed on MEDLINE, EMBASE, and the Cochrane Library (up to February 2020) without restriction on date, language, document type, and publication status. Measuring outcomes included implantation, blastulation, good-quality blastocyst formation, and euploid blastocyst. Results We detected 6 retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…), stimulation protocol, embryo culture techniques (fertilization method, culture media, gas composition), and embryo status (embryo quality and ploidy) [ 23 ]. Various authors report a lack of reproducibility between algorithms [ 24 ] or centers [ 25 ] and emphasise the need for either external validation of the models [ 26 ] or development of in-house algorithms based on the laboratory’s own data [ 27 ]. Nonetheless, the KIDScore™ (Vitrolife, Västra Frölunda, Sweden), a predictive model designed for EmbryoScope based on a large set of Known Implantation Data (KID) originating from a wide range of IVF clinics, would be universal and independent of culture conditions and fertilization methods [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…), stimulation protocol, embryo culture techniques (fertilization method, culture media, gas composition), and embryo status (embryo quality and ploidy) [ 23 ]. Various authors report a lack of reproducibility between algorithms [ 24 ] or centers [ 25 ] and emphasise the need for either external validation of the models [ 26 ] or development of in-house algorithms based on the laboratory’s own data [ 27 ]. Nonetheless, the KIDScore™ (Vitrolife, Västra Frölunda, Sweden), a predictive model designed for EmbryoScope based on a large set of Known Implantation Data (KID) originating from a wide range of IVF clinics, would be universal and independent of culture conditions and fertilization methods [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent information on human embryo selection algorithms has been summarized in several systematic reviews [ 33 , 34 , 36 , 59 ]. Several human studies have indicated that blastocyst formation can be predicted by several quantitative parameters, such as the duration of the second cleavage [ 28 , 32 , 60 ], the duration of the second synchronization (time between 3-cells to the 4-cells stage) [ 31 , 32 , 61 ], the time to 2-cell [ 61 , 62 ], and the time to 5-cells [ 60 , 61 ].…”
Section: Embryo Selection By Quantitative Parametersmentioning
confidence: 99%
“…However, a recent meta-analysis reported that TLMS interventions were effective [101]. Two randomized controlled clinical trials demonstrated the efficacy of TLMS in various conditions in the last 6 years [102,103].…”
Section: Clinical Outcomes Of Tlms and Secm Analysis In Human Ivf-et ...mentioning
confidence: 99%